2013
DOI: 10.1074/jbc.m113.492504
|View full text |Cite
|
Sign up to set email alerts
|

Human Origin Recognition Complex Binds Preferentially to G-quadruplex-preferable RNA and Single-stranded DNA

Abstract: Background: ORC binds to replication origins, but human ORC does not exhibit apparent sequence-specificity. Results: G-quadruplex (G4)-preferable RNA or single-stranded DNA competes for DNA binding of ORC. Conclusion: Human ORC binds preferentially to RNA and single-stranded DNA that form G4, and the certain domain in ORC1 is involved in this binding. Significance: This ability may correlate with the G4-formable motif in human replication origins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 43 publications
(77 reference statements)
5
89
0
3
Order By: Relevance
“…Mutagenesis studies (Valton et al 2014) will have to discern if early activation of origins in S phase is just a secondary effect of G4s influencing transcription and opening chromatin structure. ORC preferentially binds to G4s in single-stranded DNA and RNA in vitro (Hoshina et al 2013), suggesting that ORC might bind G4s in vivo. However, G4 binding of ORC was based on gel shift competition and was comparable to AT-rich dsDNA as a competitor.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis studies (Valton et al 2014) will have to discern if early activation of origins in S phase is just a secondary effect of G4s influencing transcription and opening chromatin structure. ORC preferentially binds to G4s in single-stranded DNA and RNA in vitro (Hoshina et al 2013), suggesting that ORC might bind G4s in vivo. However, G4 binding of ORC was based on gel shift competition and was comparable to AT-rich dsDNA as a competitor.…”
Section: Discussionmentioning
confidence: 99%
“…Although further research is required to determine the role of the ORC-RNA interaction in various biological processes, this data is very interesting and extends dramatically our understanding of ORC functions. Interestingly, it has recently been shown that human ORC has a much higher affinity to RNA than to either the double-stranded or single-strainded DNA in vitro [109], which encourages further investigation of RNA-ORC interactions in vivo .…”
Section: Rna-related Nonreplicative Functions Of Orcmentioning
confidence: 99%
“…Le modèle le plus probable est que dans un environnement chromatinien ouvert, le complexe ORC reconnaît aspé-cifiquement une séquence ADN. Cette interprétation est cohérente avec les données biochimiques qui ont été accumulées depuis de nombreuses années indiquant que le complexe ORC lie l'ADN indépendamment de sa séquence [1,2,37]. Ces observations suggèrent donc que le complexe ORC se lierait à la chromatine de manière opportuniste au niveau de régions de chromatine ouverte [10,38].…”
Section: Comment Se Spécifient Les Origines De Réplication ?unclassified
“…Une information de structure de l'ADN, plutôt que de séquence, permettrait donc le recrutement du complexe ORC et l'établissement des origines. Toutefois, des approches de biochimie n'ont pas permis de mettre en évidence une affinité de ORC avec des structures de ce type in vitro ( [37] …”
Section: Comment Se Spécifient Les Origines De Réplication ?unclassified